Long term outcomes of occipital nerve stimulation - Montenegro, Monique M.; Kissoon, Narayan R. (Frontiers in Pain Research, 2023)
Background Occipital nerve stimulation (ONS) has been investigated as a potential treatment for disabling headaches and has shown promise for disorders such as chronic migraine and cluster headache. Long term outcomes stratified by headache subtype have had limited exploration, and literature on outcomes of this neuromodulatory intervention spanning 2 or more years is scarce. Measures We performed a narrative review on long term outcomes with ONS for treatment of headache disorders. We surveyed the available literature for studies that have outcomes for 24 months or greater to see if there is a habituation in response over time. Review of the literature revealed evidence in treatment of occipital neuralgia, chronic migraine, cluster headache, cervicogenic headache, short lasting unilateral neuralgiform headache attacks (SUNHA) and paroxysmal hemicrania. While the term “response” varied per individual study, a total of 17 studies showed outcomes in ONS with long term sustained responses (as defined per this review) in the majority of patients with specific headache types 177/311 (56%). Only 7 studies in total (3 cluster, 1 occipital neuralgia, 1 cervicogenic headache, 1 SUNHA, 1 paroxysmal hemicrania) provided both short-term and long-term responses up to 24 months to ONS. In cluster headache, the majority of patients (64%) were long term responders (as defined per this review) and only a minority of patients 12/62 (19%) had loss of efficacy (e.g., habituation). There was a high number 313/439 (71%) of adverse events per total number of patients in the studies including lead migration, requirements of revision surgery, allergy to surgical materials, infection and intolerable paresthesias. Conclusions With the evidence available, the response to ONS was sustained in the majority of patients with cluster headache with low rates of loss of efficacy in this patient population. There was a high percent of adverse events per number of patients in long term follow-up and likely related to the off-label use of leads typically used for spinal cord stimulation. Further longitudinal assessments of outcomes in occipital nerve stimulation with devices labelled for use in peripheral nerve stimulation are needed to evaluate the extent of habituation to treatment in headache.